pTDP‐43 aggregates accumulate in non‐central nervous system tissues prior to symptom onset in amyotrophic lateral sclerosis: a case series linking archival surgical biopsies with clinical phenotypic data - Samuel B Pattle; Judi O'Shaughnessy; Owen Kantelberg; Olivia M Rifai; Judith Pate; Kristine Nellany; Nadine Hays; Mark J Arends; Mathew H Horrocks; Fergal M Waldron; Jenna M Gregory (Wiley, 2023)
Abstract Neurodegenerative diseases such as Parkinson's disease (PD), Alzheimer's disease (AD), and amyotrophic lateral sclerosis (ALS) are traditionally considered strictly neurological disorders. However, clinical presentation is not restricted to neurological systems, and non‐central nervous system (CNS) manifestations, particularly gastrointestinal (GI) symptoms, are common. Our objective was to understand the systemic distribution of pathology in archived non‐CNS tissues, taken as part of routine clinical practice during life from people with ALS. We examined tissue from 13 people who went on to develop ALS; including sporadic ALS (n = 12) and C9orf72 hexanucleotide repeat expansion (n = 1). The tissue cohort consisted of 68 formalin‐fixed paraffin embedded samples from 21 surgical cases (some patients having more than one case over their lifetimes), from 8 organ systems, which we examined for evidence of phosphorylated TDP‐43 (pTDP‐43) pathology. We identified pTDP‐43 aggregates in multiple cell types of the GI tract, including macrophages and dendritic cells within the lamina propria; as well as ganglion/neuronal and glial cells of the myenteric plexus. Aggregates were also noted within lymph node parenchyma, blood vessel endothelial cells, and chondrocytes. We note that in all cases with non‐CNS pTDP‐43 pathology, aggregates were present prior to ALS diagnosis and in some instances preceded neurological symptom onset by more than 10 years. These data imply that patients with microscopically unexplained non‐CNS symptoms could have occult protein aggregation that could be detected many years prior to neurological involvement.